ADOPTION OF ECO-INNOVATION AND DIGITALIZATION INFLUENCE ON THE BUSINESS PERFORMANCE OF UMKM IN BATAM CITY - Eryc Eryc; Cindy (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2023)
Along with the rapid economic growth, it creates competition between competitors. In this world of competition, every company must accept that there are competitors who enter the world of marketing with products that can change the basic mindset of a competitor. The only solution to solve a problem is innovation, innovation is needed by companies to be able to compete in creating a product that is superior to competitors. This study aims to find out how important eco-friendly products are and the effect of eco-innovation on the business performance of stores in Batam. This study uses a quantitative by doing the distribution of questionnaires using a purposive sampling technique. The result of the study shows that digitalization and eco-innovation have a significant effect on business performance with an index of so that it can be concluded as a satisfactory category.